Assessment of the adherence and willingness to participate in colorectal cancer screening programs among people living in prison - Giovanna Paduano; Gabriella Di Giuseppe; Mario Postiglione; Giuseppe Nese; Sabrina Morra; Maria Pavia (PLoS ONE, 2026)
This study aimed to assess the adherence and willingness to participate in colorectal cancer screening programs in people living in prison (PLP). This survey was conducted from October 2023 and July 2024. Of the 995 participating, 314 were eligible for colorectal cancer screening. Overall, 25.2% PLP had undergone a fecal occult blood test in a screening program. Those who reported consumption of at least 5 daily portions of fruit and vegetables, that were minimally active and had at least one chronic disease were significantly more likely to have undergone fecal occult blood test, whereas those who had a length of detention of 2–10 years, those who reported correct protein consumption, and those who do not drink alcohol were significantly less likely to have undergone a fecal occult blood test for colorectal cancer screening purposes. The majority (86%) expressed their willingness to undergo fecal occult blood test for screening in prison. Willingness was significantly higher in those involved in working activities in prison (OR = 4.18; 95% CI = 1.18–14.84; p = 0.027), and who had expressed willingness to receive vaccinations in prison if offered (OR = 4.4; 95% CI = 1.47–13.22; p = 0.008). Those at their first experience of detention and that had expressed their willingness to participate in interventions to promote healthy lifestyle were significantly less willing to undergo fecal occult blood test for screening purposes if offered in prison. This study highlights the need to promote health literacy on the role of cancer prevention in eligible PLP and the need for the elimination of organizational barriers.